ANALISIS PENGARUH KOMPETENSI KERJA DAN BEBAN KERJA TERHADAP PRODUKTIVITAS KERJA SURVEYOR PADA KEGIATAN CONTAINER SURVEY DI DEPO BIMARUNA JAYA - Winoto Hadi; Kencana Verawati; Rani Ismorilda (Universitas Negeri Jakarta, 2021)
Bimaruna Jaya Depot is one of the companies engaged in services related to the handling and stacking of containers. This company is currently experiencing problems regarding employee work productivity which is decreasing from month to month from the achievement target. The purpose of this study was to determine whether work competence and workload affect the work productivity of surveyors in container survey activities at Bimaruna Jaya Depot. The research method used is direct observation to the field, distributing questionnaires to insurveyors and out, estimators, andsupervisors maintenance and repair and interviews with depot managers andsupervisors maintenance and repair. The type of research used is descriptive qualitative by distributing questionnaires and interviews, namely purposive sampling technique. The results of the study indicate that the work productivity of aofficer surveyor can be influenced by competence and workload with targets set by the company.